The moral and political economy of the pandemic in Bangladesh: Weak states and strong societies during COVID-19 - Ali, Tariq Omar; Hassan, Mirza; Hossain, Naomi (Elsevier, 2022)
This article was published in World Development [©2020 Published by Elsevier Ltd. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/j.worlddev.2020.105216 The Article's website is at: https://www.sciencedirect.com/science/article/abs/pii/S0305750X20303430